Studies on Square Mesh Codend in Trawls - I Studies with 30 mm Mesh Size - K.K., Kunjipalu; M.D., Varghese; A.K., Kesavan Nair (Fishery Technology, 2025)
Covered codend experiments were conducted to determine the selective properties of 30 nun stretched square meshes compared to diamond meshes of same size. Selection curves for square and diamond meshes in respect of six finfish groups namely, Johnius spp. Leiognathus spp., Nemipterus japonicus, Sauida timibil, Dussumicria acuta and Thryssa purava; two species of prawns namely, Parapenaeopsis stylifera and Metapenaeus dobsoni and squid, Loligo sp. have been presented along with parameters such as mean selection lengths, selection ranges and selection factors. The mean selection lengths with respect to S. tumbil and D. acuta were greater in square mesh than in diamond mesh codend.